The Professional Identity Experiences of LIS Graduates in Non-Library Roles Can Be Described by the Theory of Personalizing Professionalism - Goertzen, Melissa (Evidence Based Library and Information Practice, 2018)
A Review of: Fraser-Arnott, M. (2017, May 17). Personalizing professionalism: The professional identity experiences of LIS graduates in non-library roles. Journal of Librarianship and Information Science. https://doi.org/10.1177/0961000617709062 Abstract Objective – To produce a theory that captures the professional identity experiences of library and information science (LIS) graduates employed in non-library roles. Design – Data collection and analysis were conducted using semi-structured interviews and grounded theory methodology. Setting – A variety of industry sectors located in the United States or Canada. Subjects – Twenty professionals with Master's degrees in LIS employed in non-library roles. Method – This study used the Glaserian Grounded Theory methodology, which requires constant theoretical sampling and comparison until no new data is found in any coding category. The researcher utilized two types of sampling in this study: snowball or chain referral sampling, and theoretical sampling. These techniques allowed the researcher to build a potential list of participants from a difficult to reach population. Study data was collected through semi-structured interviews divided into three sections: 1) participants were asked to describe their career experiences from their decision to attend library school to the present; 2) follow-up questions by the researcher in response to comments made by participants during the first phase; 3) questions listed in an interview guide that examined educational experiences, communities, and how participants identify themselves as professionals. Main Results – Study results produced the theory of Personalizing Professionalism, which suggests that each individual possess two identities that interact with one another throughout the course of one's career. The first is an internal appraisal of self that represents who one is as a professional. It is developed as a result of socialization in the profession and an understanding of personal motivations and interests. The second is an externally expressed identity that represents how an individual presents himself or herself to achieve professional goals. This can include self-imposed labels, such as "librarian", or strategies used to find a path within the profession. This process involves reflections and actions aimed at identifying what type of professional to be and steps required to achieve goals. The results also indicate that interactions with others impact an individual’s internal appraisal of self and externally expressed identity. Areas of conflict were identified when commonly held views of how a professional identity should be expressed did not match the identity that an individual developed or displayed to others. When conflicts arose, individuals used a variety of strategies to resolve the discrepancy between internal and external identities: assimilation, attempting to influence or change the perceptions of the group, or withdrawal. In terms of self-identifying as a librarian, the study found that participants who chose the term as a professional label believed that the work they do in non-library settings was still compatible with their definition of what it meant to be a librarian. Participants who identified as librarians some of the time and by their job title at other times did so based on an evaluation of which label would best advance their position with a given audience. Finally, participants who chose not to use the label of librarian had never internally associated with the role or job title; these individuals completed a LIS program to gain transferable skills or qualify for a wide variety of employment opportunities. Conclusion – The theory of Personalizing Professionalism provides insight into the development and expression of professional identity experiences when LIS graduates work in non-library roles. The results have value to practitioners and educators who market LIS programs or develop course content. For instance, in the future greater emphasis could be placed on transferable skill sets that are of value to roles outside of traditional library settings. Many participants described potential or actual conflicts when trying to place themselves within the LIS community because new ideas of what it means to be a “librarian” were rejected, leading to feelings of exclusion. Over time, this could lead to a detrimental loss of innovation and ideas.